Ultrasonographic parameters of the liver, spleen and kidney in a healthy paediatric population in Bosnia and Herzegovina: a prospective study - Nina Мekić; Nermin Salkić; Amela Selimović; Majda Mehmedović; Aida Brčić; Zlatan Mehmedović; Amra Šerak; Dijana Dugonjić (Medicinski glasnik, 2024)
Aim: To determine the normative range of ultrasound dimensions for the liver, spleen and kidneys in healthy children according to gender, age, body measurements, body surface area (BSA), and the influence of ethnicity on organ size. Methods: The prospective study included children, ranging from full-term neonates to children aged 15, with normal ultrasonographic (US) findings of the liver, spleen and kidney and no clinical evidence of a disease. Gender, age, as well as body measurements and BSA, were determined for each child along with US measurements, and normative ranges were established. Results: US images of the liver and spleen from 372 children and 366 US images of kidneys of 366 children were included. US measurements of the liver, spleen and kidney correlated well with gender, age, body weight and height, and often differed to a greater or lesser extent from the normal range of measurements (5th to 95th percentile) reported in other studies. Conclusion: Our results differed slightly from other reports conducted in Europe, but larger differences compared to measurements performed on children on other continents were found. Thus, our study confirmed that ethnically appropriate and modern tables of normal ultra-sound dimensions for the liver, spleen and kidneys should be used, and that the national nomogram is justified.
Keywords: elderly children; organ size; reference values; ultrasound